The influence of live streaming shopping, online customer reviews, and affiliate marketing on impulse buying trought customer trust in e-commerce shopee - Rosniati Rosniati; Heriyadi Heriyadi; Nur Afifah; Wenny Pebrianti; Harry Setiawan (International Journal of Applied Finance and Business Studies, 2023)
Marketing strategies, such as affiliate marketing and live streaming shopping, have emerged in response to the substantial amount of e-commerce consumers in Indonesia. By examining customer trust in Shopee E-Commerce, this study seeks to ascertain the impact of affiliate marketing, live streaming purchasing, and online customer reviews on impulse purchases. A total of 224 participants were enlisted for this study via an online questionnaire representing diverse regions in Indonesia. A combination of purposive and non-probability sampling methods was utilized to acquire the data for this study. Structural equation modeling (SEM) was employed to analyze the data using AMOS 22. According to this study, affiliate marketing, live streaming purchases, and online customer reviews significantly and positively influence impulsive purchasing. Meanwhile, live streaming shopping, online customer reviews, and affiliate marketing positively and significantly affect customer trust. Live streaming shopping, online customer reviews, and affiliate marketing indirectly influence customer trust and impulse buying. This research can help online business people optimize marketing in the live streaming sales and affiliate marketing industries, which are booming